Pengaruh Media Iklan dan Harga Produk Terhadap Loyalitas Konsumen PT. Coca Cola Europasific Partnership Indonesia Sumatera Utara - Ahmad Yudhira (Yayasan Grace Berkat Anugerah, 2025)
The purpose of this study was to determine the effect of the use of advertising media and product prices on consumer loyalty at PT. Coca Cola Europasific Partnership Indonesia North Sumatra. This research was conducted at PT. Coca Cola Europasific Partnership Indonesia North Sumatra, with a population and sample of 45 shops (Supermarkets, Supermarkets, Minimarkets and Restaurants) taken by census. The research instrument is a questionnaire/questionnaire with a Likert scale model. Requirements test is done by classical assumption test. Data analysis technique used is multiple regression technique at significance level = 0.05. The results of the first partial test have proven that there is an influence between advertising and loyalty seen in a significant value of 0.012 < 0.05. Thus Ha is accepted and Ho is rejected. The results of the second partial test have proven that the effect between Product Price and Loyalty has a significant effect of 0.003 < 0.05. Thus Ha is accepted, H0 is rejected. The F test proves that advertising and product prices have a simultaneous effect with a significant value of F count 0.002 <0.05 which is declared to have a positive and significant effect. Based on the SPSS output, it is known that the value of R square has an influence with a proportion of 26.3% and the excess is influenced by other factors that are not included in the research variable of 73.7%.